PENGARUH PERILAKU KOMUNIKASI PETANI TERHADAP PENGENDALIAN HAMA DAN PENYAKIT PADI SAWAH DI DESA PANGAN JAYA KECAMATAN LAINEA KABUPATEN KONAWE SELATAN - Linda; Ima Astuty Wunawarsih; Megafirmawanti Lasinta (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to determine the communication behavior of farmers and control of pests and diseases in paddy rice plants and their influence. The population in the study was all wet-rice farmers in Pangan Jaya Village, Lainea Sub-district, South Konawe Regency, which had 350 farmers. The research sample was determined as much as 10% of the population, so the sample in this study amounted to 35 people. The sample was taken using Simple Random Sampling (simple random sampling). Data collection methods use survey techniques, interviews, and documentation by utilizing research media in questionnaires. The research used a quantitative approach in its completion. Data were analyzed using descriptive analysis with the help of class interval formula and simple linear regression analysis. The results showed that the communication behavior of rice paddy farmers for information seeking, contact with extension workers, and exposure to mass media had been in the high category. This can be seen in farmers' knowledge, attitudes, and skills, each in the high category. Chemical pest and disease control carried out by wetland rice farmers is in the high category. The communication behavior of wetland rice farmers has a positive and significant effect on chemical pest and disease control.